Challenges and Opportunities of Public Sector Innovation in Fighting the Covid-19 Pandemic - Chigova, Lewis Edwin; Hofisi, Costa (International Journal of Criminology and Sociology, 2021)
The article investigates the challenges and opportunities of public sector innovation in the fight against the COVID-19 pandemic. The pandemic caused disruptions in service delivery, and public sector organisations had to find innovative ways of responding to the crisis. Through a scoping review methodology, this article unravels extant literature on some of the general innovation strategies adopted in different countries to fight the COVID-19 pandemic. The study exposes the significant challenges faced in embracing public sector innovations by reviewing many country experiences. The article then argues that public sector innovations bring about opportunities such as getting rid of obsolete systems, streamlining selected successful innovations, and galvanising reforms. The regular proactive review of public sector procedures and frameworks to permit creation is recommended.